On the electropolishing of NiTi braided stents – challenges and solutions. Issue 10 (7th October 2014) - Kassab, E.; Marquardt, A.; Neelakantan, L.; Frotscher, M.; Schreiber, F.; Gries, T.; Jockenhoevel, S.; Gomes, J.; Eggeler, G.
<x xml:space="preserve">Abstract</x> Nickel Titanium (NiTi) alloys possess special mechanical properties and good biocompatibility hence used as base material for the production of vascular stents. Normally, vascular stents are machined from NiTi tubes, using laser cutting processes. Braiding is a promising alternative for the machining of certain NiTi stents. However, a surface finish treatment, such as electropolishing of the braided stents, is still required in order to achieve a medical‐grade surface finish. The thermally‐grown oxide resulting from the shape‐setting heat treatment, following the braiding must be removed. Moreover, electropolishing is required to achieve optimum corrosion resistance. Therefore, the aim of this study is to find suitable parameters for the effective electropolishing of NiTi textile stents. Electropolishing of a device with such a complex geometry is challenging, hence a custom‐designed electrolytic cell was constructed and used in this study. We examined the stent surfaces before and after electropolishing, using scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). Potentiodynamic tests were performed in NaCl 0.9% solution for as‐received and electropolished samples. The results from the present study indicate an improvement in surface quality of the braided stents after electropolishing. Potentiodynamic tests revealed that electropolishing improves the corrosion resistance of the NiTi stents.